INTEGRASI AGAMA DAN SAINS: Bukti Kebenaran Al-Qur’an - Asyruni Multahada (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
Religion and science both have a very important role in human life. Religion is a guide or direction in life to lead an ethical, moral and civilized life. While science provides a lot of knowledge to humans, with the development of science it will advance the world with various discoveries that will facilitate and facilitate human survival. Integration seeks to create a conceptual unity between religion and science, thus leading to a re-formulation of the theological interpretation of religion. Religion is able to answer problems that science cannot answer. Religion can help science in developing scientific insights. Science can reveal the truths contained in the Qur'an, so that science can help mankind to increase their faith and devotion to Allah SWT.